2021
DOI: 10.1007/s00289-021-03975-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite of PVA/PVP blend incorporated by copper oxide nanoparticles via nanosecond laser ablation for antibacterial activity enhancement

Abstract: Polyvinyl Alcohol (PVA)/Polyvinyl Pyrrolidone (PVP) blend has been treated with various ratios of copper oxide nanoparticles (CuO NPs) via laser ablation. The spectroscopic properties of the synthesized nanocomposites were investigated by different routes. XRD confirmed the miscibility

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 62 publications
1
10
0
3
Order By: Relevance
“…The current AgNPs could have created ROS, leading to the inhibition of most pathogenic bacteria [18,43]. The results were compared with [44][45][46][47][48][49][50].…”
Section: Antibacterial Testsmentioning
confidence: 99%
“…The current AgNPs could have created ROS, leading to the inhibition of most pathogenic bacteria [18,43]. The results were compared with [44][45][46][47][48][49][50].…”
Section: Antibacterial Testsmentioning
confidence: 99%
“…Figure (4a) shows PVP characteristic absorption bands of C=O stretching vibration at 1660 cm −1 [ 31–33 ]. Stretching and scissoring vibrations of the CH 2 -CH 2 group at 2956 and 1448 cm −1 and a broad absorption band of OH stretching vibrations at 3446 cm −1 are recognized [ 34 , 35 ]. Figure (4b) shows CMC characteristic bands for OH stretching and a small band for C-H stretching at 3430 cm −1 and 2909 cm −1 , respectively, while the strong band at 1605 cm −1 is related to the COO- group.…”
Section: Resultsmentioning
confidence: 99%
“…CuO NPs have many corners and edges, high surface area, and many reactive moieties [13] . In addition, CuO NPs, which have a crystal structure, are antibacterial agents [14] . It has been reported that the antibacterial effect of CuNPs is associated with metal ions released from nanoparticles [15] .…”
Section: Introductionmentioning
confidence: 99%
“…[13] In addition, CuO NPs, which have a crystal structure, are antibacterial agents. [14] It has been reported that the antibacterial effect of CuNPs is associated with metal ions released from nanoparticles. [15] The small size and high surface area/volume ratio of CuNPs increase the antibacterial effect.…”
Section: Introductionmentioning
confidence: 99%